Influence of the weekly and match-play load on muscle injury in professional football players - Moreno-Perez, V.; Campos-Vazquez, M. A.; Toscano, J.; Sotos-Martinez, V. J.; López-Del Campo, R.; Resta, R.; Del Coso, J. (International Journal of Sports Medicine, 2022)
The aim of this investigation was to examine the impact of the weekly training load and the match running patterns prior to a muscle injury as potential risk factors of muscle injury in professional football players. Forty male professional football players participated in the investigation. Running distances at different intensities 5 min and 15 min prior to the injury were compared to the same time-points in official matches of the same player with no injury events. Furthermore, the cummulative session rating of perceived exertion (sRPE) and training load of the week prior to the injury were compared to a control week (mean value of training weeks without injury). Nineteen players suffered 31 non-contact muscle injuries during matches. The distance covered at 21-24 km/h (p<0.001; effect size (ES)=0.62) and at>24 km/h (p=0.004; ES=0.51) over the 5-min period prior to the injury was greater than in matches without injury. The cumulative sRPE (p=0.014; ES=1.33) and training volume (p=0.002; ES=2.45) in the week prior to the injury was higher than in a control week. The current data suggest that the combination of a training week with a high load and a short period of high intensity running during the match might increase the risk of muscle injury in professional footballers.